Characteristics, Management, and Outcomes of Community-Acquired Pneumonia Due to Human Rhinovirus—A Retrospective Study - Ibrahim Bahabri; Abdulaziz Abdulaal; Thamer Alanazi; Sultan Alenazy; Yasser Alrumih; Rakan Alqahtani; Mohammad Bosaeed; Hasan M. Al-Dorzi (Canadian Respiratory Journal)
Introduction. Human rhinovirus (HRV) can lead to a variety of respiratory illnesses; it is also an uncommon cause of community-acquired pneumonia (CAP). We described the characteristics and outcomes of patients hospitalized for CAP due to HRV. Methods. We retrospectively studied consecutive adult patients admitted to King Abdulaziz Medical City-Riyadh with CAP due to HRV between 2016 and 2019. The diagnosis was made by respiratory multiplex PCR within 48 hours of hospitalization. We compared patients requiring ICU admission to those who did not. Results. One-hundred-and-six patients were studied (peak hospitalization between November and January, median age 71.5 years, hypertension 59%, diabetes 50%, and chronic respiratory disease 44.3%); 16 (15.1%) patients required ICU admission. The median pneumonia severity index score (PSI) was 107, with no significant difference between ICU and nonICU patients. ICU patients had a higher prevalence of tachypnea (62.5% vs. 26.7%, p=0.005), hemoptysis (12.5% vs 0%, p=0.001), and lymphopenia (71.4% vs 26.3%, p=0.01). Chest X-ray on presentation showed bilateral infiltrates in 47/101 (46.5%) patients and unilateral infiltrates in 26/101 (25.7%) patients. Systemic corticosteroids were used in 54.7% of patients (the median initial dose was 120 mg of prednisone equivalent and was higher in nonICU patients). Most (69.2%) ICU patients received mechanical ventilation (median duration of 8 days). Bacterial coinfection (6.6%) and superinfection (3.8%) were rare. The overall hospital mortality was 9.4% (higher for ICU patients: 37.5% vs. 4.4%, p<0.001). Conclusions. Most patients with CAP due to HRV were elderly and had significant comorbidities. ICU admission was required in almost one in six patients and was associated with higher mortality.